2010
DOI: 10.1002/jcc.21504
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependent density functional theory study on the electronic excited‐state hydrogen‐bonding dynamics of 4‐aminophthalimide (4AP) in aqueous solution: 4AP and 4AP–(H2O)1,2 clusters

Abstract: The time-dependent density functional theory (TDDFT) method has been carried out to investigate the excited-state hydrogen-bonding dynamics of 4-aminophthalimide (4AP) in hydrogen-donating water solvent. The infrared spectra of the hydrogen-bonded solute-solvent complexes in electronically excited state have been calculated using the TDDFT method. We have demonstrated that the intermolecular hydrogen bond C= O...H-O and N-H...O-H in the hydrogen-bonded 4AP-(H(2)O)(2) trimer are significantly strengthened in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…4‐aminophthalimide (4AP) has been used for a range of applications since the fluorescence energies and lifetimes are sensitive to the environment, see Ref. [ ] and references therein. Wang et al have reported a 4AP–(H 2 O) 2 cluster, see Figure , which exhibits a solvatochromic red shift of about −0.29 eV in vertical excitation energies (VEEs) and −0.35 eV in vertical fluorescence energies for the S 1 state in TDDFT calculations .…”
Section: Resultsmentioning
confidence: 99%
“…4‐aminophthalimide (4AP) has been used for a range of applications since the fluorescence energies and lifetimes are sensitive to the environment, see Ref. [ ] and references therein. Wang et al have reported a 4AP–(H 2 O) 2 cluster, see Figure , which exhibits a solvatochromic red shift of about −0.29 eV in vertical excitation energies (VEEs) and −0.35 eV in vertical fluorescence energies for the S 1 state in TDDFT calculations .…”
Section: Resultsmentioning
confidence: 99%
“…Excited state calculations were done using the time-dependent DFT (TD-DFT) 54 formalism. 57,58 3. All the calculations were performed by using Gaussian09 programming package.…”
Section: Methodsmentioning
confidence: 99%
“…The theoretical calculations are useful to describe the early time hydrogen bond response to the electronic excitation and explain the mechanism of photophysical processes. In the past years, the time-dependent density functional theory (TDDFT) method is extensively employed to investigate the excited-state dynamics, which have been demonstrated a reliable tool to study the ultrafast photophysical phenomenon [20,[28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%